2016
DOI: 10.1101/073569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating resting-state functional connectivity in the cervical spinal cord at 3T

Abstract: The study of spontaneous fluctuations in the blood-oxygen-level-dependent (BOLD) signal has recently been extended from the brain to the spinal cord. Two ultra-high field functional magnetic resonance imaging (fMRI) studies in humans have provided evidence for reproducible resting-state connectivity between the dorsal horns as well as between the ventral horns, and a study in non-human primates has shown that these resting-state signals are impacted by spinal cord injury. As these studies were carried out at u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 94 publications
13
37
0
Order By: Relevance
“…From group analysis box plots of different studies, specific horn–horn functional connectivity patterns within segments appears to vary across different species. For example, the functional connectivity between ventral and dorsal horns has been observed in squirrel monkeys, whereas such connections are still speculative in humans . Similarly, in rats, ipsilateral dorsal–ventral connectivity was observed to have a weaker correlation strength, but remains statistically significant when compared with control regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From group analysis box plots of different studies, specific horn–horn functional connectivity patterns within segments appears to vary across different species. For example, the functional connectivity between ventral and dorsal horns has been observed in squirrel monkeys, whereas such connections are still speculative in humans . Similarly, in rats, ipsilateral dorsal–ventral connectivity was observed to have a weaker correlation strength, but remains statistically significant when compared with control regions.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported robust detection of rsfMRI connectivity in human subjects at ultrahigh field (7 T) using a hypothesis driven region‐of‐interest (ROI) analysis . Specifically, Barry et al found consistent functional connectivity in bilateral motor and sensory networks, while a more recent paper from Eippert et al confirmed these findings and provided further convincing evidence that spinal cord rsfMRI may be a robust technique for clinical applications . Using a similar ROI‐based approach, Liu et al reported that resting‐state networks in the upper cervical spinal cord show strong connectivity, and compared rsfMRI signals across different vertebral levels .…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord Resting‐State functional magnetic resonance imaging (rsfMRI) is a promising technique that offers a new way to investigate intrinsic spinal cord function in health and disease . However, several technical challenges still hamper its clinical application.…”
mentioning
confidence: 99%
“…31,103 What is exciting now is that we are discovering new biology-for example, the fact that the human spinal cord has intrinsically organised resting state networks. 5,33,35,63 Working at ultra high fields, such as 7 Tesla, S118 I. Tracey · 158 (2017) S115-S122 PAIN ® brings very significant signal-to-noise benefits but with new hurdles to overcome. 13 The quality of the structural pictures is sufficient to drive clinical application now and hopefully it will not take much longer before we can deliver robust and reproducible functional data from controls, experimental medicine models, and patients 141 that will contribute further towards our understanding of the role of the human spinal cord in acute and chronic pain.…”
Section: The Missing Link: Functional Neuroimaging Of the Spinal Cordmentioning
confidence: 99%